PERAN KONTROL ORANG TUA DALAM PROSES BELAJAR DARING DI ERA PANDEMI COVID-19 BAGI SISWA SEKOLAH DASAR (SD) KRISTEN TABGHA, BATAM - Johannes Hutabarat; Ista Uli Marina Aritonang; Gomgom Purba (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2023)
System learning in the network is learning that is done online with internet devices, using learning applications and social networks. Learning from home even though students' understanding is different has actually been implemented in various schools during the pandemic. Learning from home is a deliberate, conscious, planned, and directed process to improve the competence of students by taking the location of learning at home. During the online learning process, students get directions, guidelines, and study schedules from each of their educators at school, and can play a control role in the learning process by parents at home. The study schedule is the same as learning activities during the face-to-face learning period at school. The role of parental control in learning at home is important for elementary school students who are not yet capable of running online-based internet devices. Tabgha Christian Elementary School Batam under the auspices of the Indonesian Love Community Foundation was established by the leader of the Bethel Church of Indonesia, the Tabgha congregation, having its address at Komplek Cetre Park Block III number 3 Simpang Kara Batam Center who also together with the Tabgha Batam Theological College took part in the implementation of online learning in Batam. pandemic era for students. This is done to assist the central and regional governments in preventing the community from being affected by the COVID-19 virus during the learning process